2019
DOI: 10.4314/ejhs.v28i2.11
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and antimicrobial susceptibility profile of Shigella and Salmonella species from children with acute diarrhoea in Mekelle Hospital and Semen Health Center, Ethiopia

Abstract: BackgroundSalmonella and Shigella remain the major contributors to acute enteric infections and diarrhoea. Hence, the objective of this study was to isolate and determine the antimicrobial susceptibility pattern of Shigella and Salmonella species from children with acute diarrhoea in Mekelle Hospital and Semen Health Center.MethodsA cross sectional study was conducted among 260 children with acute diarrhoea from November 2011 to March 2012 in Mekelle, Ethiopia. Stool specimen was collected from all study parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 10 publications
2
17
1
1
Order By: Relevance
“…Our study revealed that the highest rates of antibiotic resistance of Shigella apps were against Ampicillin 81.8% which is comparable with the study reported from a different area of Ethiopia 70.1% from Jimma (33), 79.9% Gonder (49), 86.7% (25), and 88.9% from Mekelle (50). Our study also showed relatively low resistance compared to ndings from Nigeria 90.5% (51), Harar 100% (41), Jimma 100% (39), Hawassa 93% (34).…”
Section: Discussionsupporting
confidence: 89%
“…Our study revealed that the highest rates of antibiotic resistance of Shigella apps were against Ampicillin 81.8% which is comparable with the study reported from a different area of Ethiopia 70.1% from Jimma (33), 79.9% Gonder (49), 86.7% (25), and 88.9% from Mekelle (50). Our study also showed relatively low resistance compared to ndings from Nigeria 90.5% (51), Harar 100% (41), Jimma 100% (39), Hawassa 93% (34).…”
Section: Discussionsupporting
confidence: 89%
“…Cross sectional study design was used in all studies. The study population varied from 24 to 1200, and were conducted between the years 1999–2018 [ 15 43 ] (Table 1 ). All studies utilized stool specimens for diagnosis of Shigella species (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Natarajan M et al [14] observed that DEC is a potential diarrhoeal agent compared to other enteric bacterial pathogens in both children and adults. In other study by Gebreegziabher G et al the overall prevalence of Salmonella species was 7.3% and 6.9% Shigella species were isolated from children with diarrhoea [15] . Rotaviral infections found in our study was 23.08% it was 19 % in a study by Ghssein G et al [16] .…”
Section: Discussionmentioning
confidence: 80%